Un acercamiento al concepto de cultura - Podestá C., Paola (2006)
The following article, derived from a research conducted in an organization that belongs to the airline industry, intends to approach the concept of Culture from two theoretical viewpoints, and propose a possibility of analysis from the relation between relevant concepts of such perspectives. These afore-mentioned relations are also proposed as a reference to study cultural change in organizations. The central question impacts the concept of organizational culture and enhances a reflection: Is cultural transformation possible in an organization?